Recent Developments in Atomic Force Microscopy and Raman Spectroscopy for Materials Characterization - Shakher Pathak, Chandra; Kumar, Samir (IntechOpen, 2022)
This book contains chapters that describe advanced atomic force microscopy (AFM) modes and Raman spectroscopy. It also provides an in-depth understanding of advanced AFM modes and Raman spectroscopy for characterizing various materials. This volume is a useful resource for a wide range of readers, including scientists, engineers, graduate students, postdoctoral fellows, and scientific professionals working in specialized fields such as AFM, photovoltaics, 2D materials, carbon nanotubes, nanomaterials, and Raman spectroscopy.